2004
DOI: 10.1002/app.20124
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, hygroscopic, and thermal properties of metal particle and metal evaporated tapes and their individual layers

Abstract: Mechanical and thermal properties of magnetic tapes and their individual layers strongly affect the tribology of magnetic head-tape interface and reliability of tape drives. Dynamic mechanical analysis, longitudinal creep, lateral creep, Poisson's ratio, the coefficient of hygroscopic expansion (CHE), and the coefficient of thermal expansion (CTE) tests were performed on magnetic tapes, tapes with front coat or back coat removed, substrates (with front and back coats removed), and never-coated virgin films of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Previous experiments conducted with commercial DMA equipment have shown these trends, as the storage modulus slope is fairly stable until it reaches an elevated temperature near 100°C, when more energy is released, and the slope of the elastic modulus becomes more negative 3, 6–8, 17. This is also reflected in the loss tangent plots, where the peak of the α‐peak aligns with the temperature at which the storage modulus slope changes.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Previous experiments conducted with commercial DMA equipment have shown these trends, as the storage modulus slope is fairly stable until it reaches an elevated temperature near 100°C, when more energy is released, and the slope of the elastic modulus becomes more negative 3, 6–8, 17. This is also reflected in the loss tangent plots, where the peak of the α‐peak aligns with the temperature at which the storage modulus slope changes.…”
Section: Resultsmentioning
confidence: 67%
“…By performing experiments at different temperatures, information about the magnetic tape samples' thermal properties, such as their glass transition temperatures, could be extracted. Experiments from commercial DMAs have shown shifts in the relaxation peaks (α, β, and β*) to lower temperatures, associated with decreased strain application frequencies 3, 6, 7, 17. Therefore, by performing ULDMA experiments along frequency and temperature sweeps, the storage modulus, loss modulus, and loss tangent values can be plotted against temperature, demonstrating how decreased frequencies influence these peaks.…”
Section: Resultsmentioning
confidence: 99%
“…Hu and Hollman (1984) examined the case of a curved tape segment and noted that a tension gradient will develop across the tape width as a result of uneven stretching. Bhushan (1992) concluded that uneven tension across the tape width can cause tape vibration over the guide bearings. Our experimental results showed that a correlation exists between tape tension transients and LTM, although no prediction could be made about the direction of the motion resulting from a tension transient.…”
Section: Discussionmentioning
confidence: 98%
“…If one edge of a tape is shorter than the other, the tape is curved (Bhushan 1992). Curvature can be characterized by the radius of curvature, denoted as r in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation